Milton's imperial epic Paradise lost and the discourse of colonialism - Evans, John M. (Cornell Univ. Press, 1996)
In the opinion of J. Martin Evans, Paradise Lost is at heart a poem about empire. Written during the crucial first phase of English empire-building in the New World, Milton's epic registers the radically divided attitudes toward the settlement of America that existed in seventeenth-century Protestant England. Evans looks at the relationship between Paradise Lost and the pervasive colonial discourse of Milton's time. Evans bases his analysis on the literature of exploration and colonialism. The primary sources on which he draws range from sermons about the New World justifying colonization and exhorting virtue among colonists to promotional pamphlets designed to lure people and investment into the colonies. Evans's research allows him to create a richly textured picture of anxiety and optimism, guilt and moral certitude. The central question is whether Milton supported England's colonization or covertly attempted to subvert it. In contrast to those who attribute to Paradise Lost a specific political agenda for the American colonies, Evans maintains that Milton reflects the complexity and ambivalence of attitudes held by English society. Analyzing Paradise Lost against this background, Evans offers a new perspective on such fundamental issues as the narrator's shifting stance in the poem, the unique character of Milton's prelapsarian paradise, and the moral and intellectual status of Adam and Eve before and after the Fall. From Satan's arrival in Hell to the expulsion from the garden of Eden, Milton's version of the Genesis myth resonates with the complex thematics of Renaissance colonialism.
Keywords: Milton, John <1608-1674> - Pensée politique et sociale; Milton, John <1608-1674> - Political and social views; Milton, John <1608-1674> / Paradise lost; Milton, John <1608-1674> -- Paradise lost; Milton, John -- 1608-1674 -- Paradise lost; Colonies dans la littérature; Impérialisme dans la littérature; Kolonialisme; Paradise lost (Milton); Poésie épique anglaise - Histoire et critique; Colonies in literature; Epic poetry, English -- History and criticism; Fall of man in literature; Imperialism in literature; Political poetry, English -- History and criticism; Kolonialismus -- Motiv; Kolonialismus